Clinical Effect of Electroacupuncture on Acute Sleep Deprivation and Event-Related Potential Affecting the Inhibition Control of the Brain: Study Protocol for a Randomized Controlled Trial - Li, Haiping; Wang, Mengyu; Wu, Yiming; Chen, Xinwang; Xue, Cong; Liu, Peidong; Zhang, Run; Liao, Ziyun (Frontiers in Neurology, 2022)
Background: Acute sleep deprivation (ASD) can effect mood, attention, memory, alertness and metabolism. Especially, it is often accompanied by cognitive impairment of the brain. Acupuncture is safe and effective for improving cognitive function, but its underlying mechanism is not fully understood. In this study, an event-related potential (ERP) technique will be employed to measure the behavioral, cognitive, and physiological changes produced by electroacupuncture intervention after ASD. Methods: We will recruit 45 healthy subjects. The participants will be randomly divided into a treatment group, a control group and a blank group, at a 1:1:1 ratio. The primary outcome will be determined by the change from baseline to 36 hour in the MoCA score. The secondary results include the amplitude and latency of ERP N2 and P3, Go-hit rates, Go-RTs, No-Go-FA rates, the ESS score and FS-14. The 15 healthy subjects will not receive acupuncture treatment, but will receive EEG records and a MoCA test at the beginning and end of the experiment. Electroacupuncture intervention will be performed for 30min once every 12 h, a total of three times. ERP measurements and other tests will be performed after baseline and ASD, and the statistician and outcome evaluator will be blinded to treatment allocation. Discussion: This study is expected to investigate the effectiveness of electroacupuncture in improving cognition for ASD.